Clinical and Ultrastructural Characteristics of Graft Failure in DMEK: 1-Year Results After Repeat DMEK - Cirkovic, Aleksandar; Schlötzer-Schrehardt, Ursula; Weller, Julia M.; Kruse, Friedrich; Tourtas, Theofilos (Cornea, 2015)
To evaluate the role of preexisting corneal pathology on the outcome of Descemet membrane endothelial keratoplasty (DMEK), and also to evaluate the long-term outcome of repeat DMEK for graft failure after primary DMEK.Eighteen patients undergoing repeat DMEK after failed DMEK were enrolled; 9 of 18 patients had successful primary DMEK on the fellow eye. Evaluations included preoperative anterior chamber depth, intraoperative degree of difficulty, transmission electron microscopy images (n = 14), best-corrected visual acuity (BCVA), endothelial cell density, central corneal thickness, corneal volume, and patient satisfaction.Surgeries that led to graft failure had a higher intraoperative degree of difficulty compared with successful surgeries (P = 0.002). Eight of 14 failed grafts showed ultrastructural abnormalities, that is, inclusions or deposits of abnormal fibrillar material in Descemet membrane, indicating endothelial dysfunction before transplantation. BCVA on day 10 after surgery was worse in eyes with graft failure compared with successful DMEK (P = 0.008). Median BCVA (logarithm of the minimum angle of resolution) improved from 0.5 before DMEK and 1.9 before repeat DMEK to 0.3 at 1-year follow-up (P = 0.011). One year after repeat DMEK, endothelial cell density (cells/mm) of donor corneas decreased from 2501 ± 264 to 1373 ± 270 (P < 0.001), central corneal thickness (µm) decreased from 807 ± 160 to 576 ± 178 (P = 0.002), and corneal volume (mm) decreased from 84.1 ± 13.0 to 64.4 ± 12.5 (P = 0.002). Patient satisfaction showed no difference between primary and repeat DMEK.A preexisting subclinical corneal endothelial dysfunction may contribute to primary DMEK failure. Repeat DMEK can be performed safely with good long-term outcome.
EVALuna2:21222